Microfilariae infection by Acanthocheilonema reconditum and Dirofilaria immitis and their molecular detection in a dog with lymphoma: Case report (Journal of Advanced Veterinary and Animal Research, 2023)
Objective: Microfilariae parasites are common in tropical regions, and some species are reported as potentially zoonotic. The diagnosis of filarial infection in dogs by cytology or hematologic techniques showed lower sensibility and specificity, which may result in misdiagnosis. Thus, molecular techniques seem to be an alternative to identifying and detecting microfilariae infections. On the other hand, lymphoma is one of the main tumors in domestic animals, with a high prevalence in domestic canines. This study aims to report a mixed infection with microfilariae in a dog with lymphoma, emphasizing its diagnosis and the possible role of this infection in the development of the neoplasia. Materials and Methods: An 8-year-old male mixed breed dog was referred to consultation due to the presence of lethargy, recumbency, skin ulceration lesions, nonspecific pain manifestations, emesis, myoclonus in the left temporalis muscle, and seizures. Routine blood and biochemistry tests were normal, and cytology of the skin evidenced a microfilariae infection. The dog died due to a cardiorespiratory arrest, and tissue sampling was done for histopathology and molecular analysis at the necropsy examination. Results: Skin lesions were related to a microfilarial pyogranuloma related to Acanthocheilonema reconditum. Histopathology of the spleen and liver revealed a diffuse lymphoma composed of blast cells and large lymphocytes, distributed diffusely in the parenchyma and surrounding the vasculature. In the skin, microfilariae were seen in some superficial capillaries. Conclusion: This study describes a microfilariae mixed infection with A. reconditum and Dirofilaria immitis in a dog with a lymphoma and its molecular detection. To the knowledge of the authors, this is the first report of a mixed microfilariae infection in a tumor of a dog and highlights the use of molecular techniques, i.e., polymerase chain reaction, for an accurate diagnosis.J. Adv. Vet. Anim. Res., 10(3): 484–489, September 2023http://doi.org/10.5455/javar.2023.j701